Separation of fingerprint constituents using magnetic silica nanoparticles and direct on-particle SALDI-TOF-mass spectrometry - Lim, Angelina Yimei (2011)
Two types of amorphous, silica nanoparticles have been produced and used as surface assisting agents during laser desorption/ionisation time-of flight-mass spectrometry (SALDI-TOF-MS). The first is hydrophilic possessing surface aminopropyl groups and the second hydrophobic containing surface phenyl groups. Each particle type acts as a solid phase adsorbent, adsorbing analytes according to their charge and hydrophobicity. The adsorbed analytes can be directly analysed on the particles using SALDI-TOF-MS. Intrinsically magnetisable versions of the hydrophobic particles act as magnetic solid phase extraction (MSPE) materials which are used to selectively adsorb analytes within a mixture deposited onto a surface, transfer the adsorbed components using a magnetic wand and to deposit the particles at a site adjacent to that of the original mixture. Non-adsorbed components remain at the original site. The extracted and residual analytes are then directly analysed on the surface by SALDI-TOF-MS. Using fingerprints as an example of a complex biological matrix, this new approach has been used to separate polar (amino acids) and non-polar constituents (squalene and fatty acids) within latent fingerprints deposited on a surface and for their subsequent direct analysis on the surface by SALDI-TOF-MS. Alanine, ornithine, lysine and aspartic acid which were undetected or poorly detected prior to separation showed improved signal detection after separation.